Digitalisasi Manajemen Sampah 3R Berbasis Mobile di Lingkungan Sekolah - Sugiyatno Sugiyatno; Mega Wahyu Rhamadani; Ridwan Ridwan; Prima Dina Atika (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2026)
Waste management in schools is an important effort to develop environmental awareness among students from an early age. However, many students still lack awareness and habits in identifying and recording the types and quantities of waste generated in their daily activities. Therefore, an educational medium based on digital technology is needed to support students in understanding and managing waste more effectively. This community service activity aimed to implement a mobile-based application for recording waste using the 3R (Reduce, Reuse, Recycle) principle in the school environment. The methods used in this program included socialization, environmental education, and demonstrations on how to use the application for students and teachers at Sekolah Islam Al-Azhar BSD@Cileungsi, Bogor Regency. The mobile application introduced in this activity provides several main features, including user registration and login, input of waste types such as organic, inorganic, and hazardous waste (B3), and daily waste data recapitulation. The results of the activity indicate that the implementation of the mobile application increased students’ understanding and awareness of waste management while encouraging active participation in applying the 3R principles within the school environment. In addition, the application helps organize waste recording more systematically and allows easier monitoring by the school management. Therefore, the implementation of a mobile-based waste recording application can serve as an innovative solution to support environmental education and improve waste management practices in schools.